Lowering charge transfer barrier of LiMn2O4 via nickel surface doping to enhance Li+ intercalation kinetics at subzero temperatures - Zhang, Wei (2020)
Sluggish interfacial kinetics leading to considerable loss of energy and power capabilities at subzero temperatures is still a big challenge to overcome for Li-ion batteries operating under extreme environmental conditions. Herein, using LiMn2O4 as the model system, we demonstrated that nickel surface doping to construct a new interface owning lower charge transfer energy barrier, could effectively facilitate the interfacial process and inhibit the capacity loss with decreased temperature. Detailed investigations on the charge transfer process via electrochemical impedance spectroscopy and density functional theory calculation, indicate that the interfacial chemistry tuning could effectively lower the activation energy of charge transfer process by nearly 20%, endowing the cells with ∼75.4% capacity at −30 °C, far surpassing the hardly discharged unmodified counterpart. This control of surface chemistry to tune interfacial dynamics proposes insights and design ideas for batteries to well survive under thermal extremes.